Synthesis and biological evaluation of cis-restrained carbocyclic combretastatin A-4 analogs: Influence of the ring size and saturation on cytotoxic properties - Nowikow, Christina; Fuerst, Rita; Kauderer, Maria; Dank, Christian; Schmid, Walther; Hajduch, Marian; Rehulka, Jiri; Gurská, Soňa; Mokshyna, Olena; Polishchuk, Pavel; Zupkó, István; Dzubak, Petr; et al. (Bioorganic & medicinal chemistry, 2019)
Combretastatin A-4 (CA-4) is a highly cytotoxic natural product and several derivatives have been prepared which underwent clinical trial. These investigations revealed that the cis-stilbene moiety of the natural product is prone to undergo cis/trans isomerization under physiological conditions, reducing the overall activity of the drug candidates. Herein, we report the preparation of cis-restrained carbocyclic analogs of CA-4. The compounds, which differ by the size and hybridization of the carbocyclic ring have been evaluated for their cytotoxic properties and their ability to inhibit tubulin polymerization. Biological data, supported by molecular docking studies, identified cyclobutenyl and cyclobutyl derivatives of the natural product as highly promising drug candidates.
Keywords: Tubulin; kontrolní body fáze G2 buněčného cyklu; Cell Line, Tumor; screeningové testy protinádorových léčiv; simulace molekulového dockingu; vazba proteinů; Molecular Structure; stilbeny; lidé; Antineoplastic Agents; protinádorové látky; Stilbenes; molekulární struktura; tubulin; Tubulin Modulators; G2 Phase Cell Cycle Checkpoints; modulátory tubulinu; Drug Screening Assays, Antitumor; Protein Binding; Molecular Docking Simulation; nádorové buněčné linie; Humans